Urgensi Pengembangan Rubrik Asesmen Multiliterasi untuk Mendukung Pembelajaran STEAM pada Mata Pelajaran IPAS: Studi Kasus di Kelas V SD Negeri Kemirisewu II Pasuruan - Ratna Sari Dewi; Intan Sari Rufiana; Sri Rahayuningsih (Journal of Practice Learning and Educational Development, 2026)
Assessment practices in STEAM-based science learning (IPAS) in grade V of elementary schools are still dominated by conventional written tests that focus on final cognitive outcomes. This study aims to analyze the urgency of developing a multiliteracy assessment rubric in the context of STEAM-based IPAS learning in grade V of SD Negeri Kemirisewu II Pasuruan. This research employs a qualitative approach with a case study type. Data sources include primary data (fifth-grade teacher and two student representatives) and secondary data (teaching modules, evaluation sheets, and documentation). Data collection techniques included non-participant observation, semi-structured interviews, and documentary study. The findings reveal three main points. First, there is a gap between STEAM-oriented learning design and assessment practices that still rely on written tests. Second, aspects of collaboration, critical thinking, and creativity have not been systematically measured due to the teacher's lack of assessment rubrics. Third, the challenges faced by the teacher include time constraints, a large number of students, a lack of assessment instrument examples, and the absence of multiliteracy assessment training. The development of a multiliteracy assessment rubric is an urgent necessity at the research site. The rubric developed must be valid, practical, and aligned with the characteristics of the STEAM approach to assess students' collaboration, critical thinking, creativity, and communication processes objectively, systematically, and sustainably.